THERAPY AT THE CULTURAL INTERFACE: IMPLICATIONS OF AFRICAN COSMOLOGY FOR TRAUMATIC STRESS INTERVENTION - Eagle, Gillian (PINS-Psychology in Society, 2026)
Within· the field of psychotherapy the topic of intercultural or multicultural therapy continues to stimulate much debate. One of the key themes that is constantly revisited is whether psychotherapies derived primarily from Eurocentric and essentially Western orientations are applicable to people from non-Western cultures. Such questioning concerns not only the theoretical premises upon which understanding of pathology and distress are based, but also aspects of the style and process of intervention. Based upon clinical experience of direct intervention and supervision in the trauma field in South Africa over some 20 years, this paper seeks to contribute to this debate by examining a specific kind of dilemma and a specific arena of intervention. The dilemma arises out of critical observations of circumstances in which conventional African wisdom, as understood by clients presenting for trauma counselling, appeared to be counterproductive for their recovery in terms of western intervention principles. Almost invariably intercultural counselling training emphasizes respect for cultural beliefs as a core dimension of appropriate intervention. The therapist is thus confronted by a particularly difficult dilemma when faced with a clinical situation in which the non challenging of cultural belief systems seems counter-therapeutic. How does one subscribe to the imperative to respect alternative cosmologies whilst retaining therapeutic integrity in terms of being informed by rigorous theory and pursuing the best interests of the client? Within the arena of psychotherapy for traumatic stress, including traumatic bereavement, such tensions appear to arise particularly strongly because of the inevitable search for meaning in the face of extraordinary life events. Focusing particularly on aspects of meaning making, cognitive intervention, schema realignment and reframing within trauma therapy, the paper elaborates areas of potential conflict with reference to both theory and clinical case material. Aspects of causal attributions for misfortune and their implications as understood both within African cosmology and within Western trauma theory frameworks are counterpoised. Having highlighted central points of tension in working at this cultural interface, the paper concludes with some suggestions as to how to manage such complexities in intercultural therapeutic work A clinical case example is drawn upon to illustrate how a particular therapist-client dyad negotiated this tension in the course of a short-term psychotherapy.